Metallic Powders for Additive Manufacturing: Science and Applications - Lavernia, Enrique J; Ma, Kaka; Schoenung, Julie M; Shackelford, James F; Zheng, Baolong (John Wiley & Sons, Incorporated, 2024)
Metallic Powders for Additive Manufacturing Overview of successful pathways for producing metal powders for additive manufacturing of high-performance metallic parts and components with tailored properties Metallic Powders for Additive Manufacturing introduces the readers to the science and technology of atomized metal powders beyond empirical knowledge and the fundamental relationships among the chemistry, microstructure, and morphology of atomized metallic powders and their behavior during additive manufacturing. The text sets a foundation of the underlying science that controls the formation and microstructure of atomized metallic droplets, including the relations among the properties of metallic powders, their performance during the manufacturing processes, and the resulting products. Other topics covered include the influence of powder on defect formation, residual stress, mechanical behavior, and physical properties. The concluding two chapters encompass considerations of broader societal implications and overarching themes, including the exploration of alternative feedstock materials, economic analysis, and sustainability assessment. These chapters offer valuable perspectives on the prospective trajectory of the field. Written by a team of experienced and highly qualified professors and academics, Metallic Powders for Additive Manufacturing includes information on: Atomization techniques such as Vacuum Induction Gas Atomization (VIGA), Electrode Induction Melting Gas Atomization (EIMGA), and Plasma Rotating Electrode Process (PREP) Atomization science and technology, covering control of atomization parameters, powder size distribution, effect of processing variables, and theoretical models of atomization Heat transfer and solidification of droplets, covering nucleation, microstructure development, and important thermal and solidification conditions during atomization Atomization of Al, Fe, Ni, Co, Ti, and high entropy alloys, as well as composite powders for additive manufacturing, and guidelines for atomization equipment and powder handling Fundamental processing principles in a variety of metal additive manufacturing processes Powder characteristics and requirements for different additive manufacturing processes Effect of powder chemistry and physical characteristics on additive manufacturing processes, and the microstructure and properties of the built parts Evaluation of alternative feedstock sources for metal additive manufacturing, beyond gas atomized powder Economic and sustainability perspectives on powder production and additive manufacturing Metallic Powders for Additive Manufacturing is an excellent combination of rigorous fundamentals and a practice-oriented and forward-looking resource on the subject for materials scientists and practicing engineers seeking to understand, optimize, and further develop the field of powder production and additive manufacturing.